Analysis of Digital Media Utilization in Enhancing Language Skills of 4 Year Old Children at PAUD IT Al Multazam Kuningan - Hafidhoh, Husnul; Fatahillah, Mubarok (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2025)
Background: The use of digital media in early childhood education continues to expand, yet its role in enhancing language skills within Indonesian Islamic preschool settings remains limited in scholarly attention, especially for 4-year-old children who are at a critical stage of language growth.Objective: This study examines the utilization of digital media to support the language development of 4-year-old children at PAUD IT Al Multazam Kuningan through a qualitative case study involving semi-structured interviews with four teachers, administrators, and eight parents, supported by classroom observations and document analysis.Method: Data were processed using Miles, Huberman, and Saldaña’s interactive model.Findings and Implications: The findings show that the institution adopted a structured digital media program consisting of Morning Circle Digital Literacy, Story Time Enhancement, and Language Lab Activities. This approach contributed to measurable language gains, including monthly vocabulary growth, improved expressive and receptive language performance, and better pragmatic communication. Key enabling factors included adult co-viewing, dialogic questioning, and the integration of Islamic values along with dual-language exposure in Indonesian and Arabic.Conclusion: The study highlights that the effectiveness of digital media depends on purposeful pedagogical integration, sustained professional development, and stakeholder collaboration within an Islamic educational framework.